Clinical cancer immunotherapy: Current progress and prospects - Liu, Chenglong; Yang, Mengxuan; Zhang, Daizhou; Chen, Ming; Zhu, Di (Frontiers in Immunology, 2022)
Immune checkpoint therapy via PD-1 antibodies has shown exciting clinical value and robust therapeutic potential in clinical practice. It can significantly improve progression-free survival and overall survival. Following surgery, radiotherapy, chemotherapy, and targeted therapy, cancer treatment has now entered the age of immunotherapy. Starting from cancer immunotherapy, this paper discusses the basic classification, research progress, and future prospects for new anticancer immunotherapy methods and provides a reference for the future drug development of cancer immunotherapy.